Gewerkschaftliches Interessenhandeln im Bereich kommunaler Kindertagesstätten – Voraussetzungen, Formen, Ergebnisse; Unions' activities in the German public day-care sector – pre-conditions, forms, outcomes - Stefan Kerber-Clasen (Industrielle Beziehungen, 2014)
Ausgehend von einer Analyse der Spezifika des Interessenhandelns bei interaktiver Sorge- und Bildungsarbeit sowie der jüngsten strukturellen Veränderungen des Kita- Bereichs wird das gewerkschaftliche Interessenhandeln im kommunalen Kita-Bereich fokussiert. Als dessen sichtbarster und entschiedenster Ausdruck der vergangenen Jahre wird der Kita- Streik von 2009 untersucht. Die Forderungen der Streikenden, die Arbeitsbedingungen und die Entlohnung zu verbessern, wurden nur in Ansätzen erfüllt, positive Ergebnisse waren hingegen die Aktivierung und Politisierung der Beschäftigten sowie die öffentlich geäußerte symbolische Anerkennung der Arbeit. Die Fortsetzung gewerkschaftlichen Interessenhandelns in den kommenden Jahren kann so auf einer – verglichen mit anderen sozialen Dienstleistungen – relativ starken gewerkschaftlichen Organisierung und Aktivierung aufbauen. Empirisch stützt sich die Analyse vor allem auf halb-strukturierte Interviews mit haupt- und ehrenamtlichen GewerkschafterInnen von ver.di und der GEW. – – How do unions and unionized employees in the public day-care sector pursue their interests within the changing day-care sector? In a first step, the article analyzes the characteristics of interactive service/care work and its inherent possibilities for agency in the sense of pursuing employees' interests. These insights into the possibilities for union activities in this sector are complemented by the discussion of recent developments of the day-care sector: the implementation of educational curricula, the expansion of the sector by granting children from the age of one the right to attend a day-care institution and the shortage of qualified labour. These are the new material basis for union activities. As the most prominent example of union activities, the federal strike in the day-care sector of 2009 (Kita-Streik) is analyzed in detail. Positive elements of the strike were the vast participation of employees, their increased political awareness regarding their work and employment and the public recognition employees gained during the strike. Further union activities may build on these experiences, especially as unions plan to intensify their efforts to enhance employees' pay and working conditions in the years to come. The article draws upon qualitative empirical data, especially semi-structured interviews with union officials and union activists.
Keywords: J13; J45; J52; 330; public day care; employees` agency; (trade) union; strike